Real-World Efficacy of Midostaurin in Aggressive Systemic Mastocytosis - Szudy-Szczyrek, Aneta (J Clin Med, 2021)
In April 2017 midostaurin was approved by the US Food and Drug Administration for the treatment of patients with aggressive systemic mastocytosis (ASM). So far, very limited real world data on its efficacy is available. Thirteen patients aged from 48 to 79 years, who received midostaurin in the early access program, were included in the study. Midostaurin was used both in first (n = 5) and subsequent lines of treatment (n = 8). The median duration of exposure was 9 months. Most patients (77%, n = 10) had a clinical improvement already as soon as the second month of therapy. Objective response was noted in 4 (50%) of eight evaluated patients. Among responders, we observed a decrease in serum tryptase level (median 74.14%) and bone marrow infiltration by mast cells (median 50%) in the sixth month of treatment. In one case, in the 10th month of treatment, allogenic stem cell transplantation was performed, achieving complete remission. Five patients died, three due to progression of disease, one in the course of secondary acute myeloid leukemia and one due to reasons not related to mastocytosis. Treatment is ongoing in seven patients. We found that midostaurin therapy is beneficial to patients with ASM.